Comparative Studies of Collective Mentality: Travel Letters of Konstantin Bogdanović - Kostadinović, Aleksandar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper analyzes the travel letters of Konstantin Bogdanović (1811–1854), a Serbian lawyer, writer, publicist, and politician who is regarded in literary historiography as one of the founders of Serbian literary criticism. Despite their significance, his travel writings have received little scholarly attention thus far. His two articles, “Letters from Paris” and “Letters from London”, which were published serially in Theodor Pavlović’s Serbski narodni list in 1846, represent the genesis of Serbian travel epistolography, particularly those written intentionally for publication in periodicals. The paper focuses on imagotypical elements in Bogdanović’s texts, analyzing French and English national characters comparatively. Using the methodology of comparative imagology, the paper explores the social, political, and literary factors that shaped the hetero-images of these two European nations in Bogdanović’s travel letters.
Keywords: 19th-century Serbian travel literature; travel letter; imagology; national character; imagotype; hetero-image; Konstantin Bogdanović